ANALISIS KESALAHAN SINTAKSIS PADA PENULISAN TEKS FABEL SISWA KELAS VII SMP SOMBA OPU KABUPATEN GOWA: ANALYSIS OF SYNTACTIC ERRORS IN THE WRITING OF FABLE TEXTS OF STUDENTS IN CLASS VII SMP SOMBA OPU GOWA DISTRICT - Ikhsan Basir, Muh. Nur; Djumingin, Sulastriningsih; Fitri, Sakinah (Journal of Applied Linguistics and Literature, 2024)
his study aims to describe phrase errors in syntax in the writing of fable texts of Class VII students of SMP Somba Opu Gowa Regency, describe sentence errors in syntax in the writing of fable texts of Class VII students of SMP Somba Opu Gowa Regency. This type of research is qualitative by using descriptive method. The instrument in this research is the researcher (human instrument). Data collection techniques in this study used observation, documentation, reading, and note-taking methods. Data analysis uses data analysis techniques based on Miles and Huberman in the form of data reduction, data validity, and conclusion drawing. The results showed phrase errors in the writing of fable texts of seventh grade students of SMP Somba Opu Gowa Regency, and sentence errors in the writing of fable texts of seventh grade students of SMP Somba Opu Gowa Regency. Phrase errors in syntax include six types of errors, namely: the influence of local language, inaccurate use of prepositions, inaccurate phrase structure, excessive use of elements, excessive use of superlative forms and inaccurate use of reciprocal forms. Sentence errors in syntax include five types of errors, namely sentences without subjects, illogical sentences, ambiguous sentences, excessive use of conjunctions, and non-parallel sentence order.